Development and Characterization of Boron-Nitride Reinforced Nickel Matrix Composites - Uz Zaman Atteeq; Khan Awais; Zaman Fatima; Khan Muhammad Moheen; Farooq Umar; Shehbaz Tauheed; Karim Muhammad Ramzan Abdul (MATEC Web of Conferences, 2023)
In this work, pure nickel was reinforced with various contents of h-BN (4 & 8wt.%) and SiC (2, 4, 6 & 8wt.%) prepared via PM route. The synergistic effect of h-BN and SiC on mechanical and microstructural behaviour was investigated. The microstructure and crystal structure were characterized by scanning electron microscope and X-ray diffractometer. The density and microhardness were eveluated via He pycnometer and microhardness tester. SEM results revealed that the exfoliation reduced the particle size of h-BN from approximately 105 nm to 30-40 nm. Furthermore, the addition of h-BN and SiC improved the mechanical properties of the composite. The maximum hardness value of 420 HV was obtained for Ni-8BN-6SiC. This improvement in hardness was attributed to uniform dispersion and high hardness of h-BN and SiC. However, more addition of SiC (>6 wt.%) deteriorated the hardness of the composite due to generated porosity.